1969
DOI: 10.12669/pjms.303.4931
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Patterns of General Practitioners in Peshawar, Pakistan

Abstract: Objectives: To find out prescription patterns of general practitioners in Peshawar. Methods: Cross-sectional survey of drug prescriptions was done at six major hospitals and pharmacies of Peshawar between April and May 2011. A total of 1097 prescriptions that included 3640 drugs, were analyzed to assess completeness, average number of drugs, prescription frequency of various drug classes, and number of brands prescribed. Results: No prescription contained all essential components of a prescription. Legibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 1 publication
3
35
0
1
Order By: Relevance
“…This is a follow-up to our previous study [35] that highlighted the low level of completeness and legibility of drug prescriptions in the same geographical area. The current study was designed to assess the effect of introducing an intervention (a pre-printed structured prescription form) on the level of completeness and legibility of prescriptions.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This is a follow-up to our previous study [35] that highlighted the low level of completeness and legibility of drug prescriptions in the same geographical area. The current study was designed to assess the effect of introducing an intervention (a pre-printed structured prescription form) on the level of completeness and legibility of prescriptions.…”
Section: Discussionsupporting
confidence: 57%
“…The results indicated that in 89% of prescriptions, doctor's name was not written . In 79%, diagnoses were not mentioned, and in 55% and 11%, duration and directions for taking drugs were not mentioned, respectively . The results of the study also indicated that one of the locations assessed in the study had better quality of prescriptions, and this was the only location using structured prescription forms.…”
Section: Introductionmentioning
confidence: 85%
“…54 In our present study most of the drugs (92%) were prescribed by brand name which coincides with the report from the survey conducted by previous study. 54,55 A total number of 473antibiotic drugs were found in 300 prescriptions among which antibiotics that lie under β-Lactam class were most commonly prescribed. A similar incident was reported in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In above scenario nurse was de-motivated because nurse manager was having bias attitude toward their staff as well as and not interested to provide them the opportunities for promotion. A study conducted at Khyber Teaching Hospital, Raza [3] shows that nurses were dissatisfy due to the lack of promotion opportunities and low salary. Nurses were unsatisfied because of slow procession and unfair means used to avail the Promotion opportunities although they are eligible and meeting the criteria.…”
Section: Forensic Sci Add Resmentioning
confidence: 99%